Embodied multicultural assessment: An interdisciplinary training model. Issue 1 (1st April 2016) - Powell, Alexis
Cross-cultural counselling is imperative in the training of any therapist, yet there are no educational models based on drama therapy techniques. The author explores the need for an embodied multicultural self-assessment for drama therapy students and presents an approach that incorporates Robert Landy's role theory and Pamela A. Hays' ADDRESSING framework.